Opinion review of drug resistant tuberculosis in West Africa: tackling the challenges for effective control - Otchere, Isaac Darko; Asante-Poku, Adwoa; Akpadja, Kodjo Francis; Diallo, Awa Ba; Sanou, Adama; Asare, Prince; Osei-Wusu, Stephen; Onyejepu, Nneka; Diarra, Bassirou; Dagnra, Yaotsè Anoumou; Kehinde, Aderemi; Antonio, Martin; et al. (Frontiers in Public Health, 2024)
Drug-resistant (DR) tuberculosis (TB) is a major public health concern globally, complicating TB control and management efforts. West Africa has historically faced difficulty in combating DR-TB due to limited diagnostic skills, insufficient access to excellent healthcare, and ineffective healthcare systems. This has aided in the emergence and dissemination of DR Mycobacterium tuberculosis complex (MTBC) strains in the region. In the past, DR-TB patients faced insufficient resources, fragmented efforts, and suboptimal treatment outcomes. However, current efforts to combat DR-TB in the region are promising. These efforts include strengthening diagnostic capacities, improving access to quality healthcare services, and implementing evidence-based treatment regimens for DR-TB. Additionally, many West African National TB control programs are collaborating with international partners to scale up laboratory infrastructure, enhance surveillance systems, and promote infection control measures. Moreso, novel TB drugs and regimens, such as bedaquiline and delamanid, are being introduced to improve treatment outcomes for DR-TB cases. Despite these obstacles, there is optimism for the future of DR-TB control in West Africa. Investments are being made to improve healthcare systems, expand laboratory capacity, and support TB research and innovation. West African institutions are now supporting knowledge sharing, capacity building, and resource mobilization through collaborative initiatives such as the West African Network for TB, AIDS, and Malaria (WANETAM), the West African Health Organization (WAHO), and other regional or global partners. These efforts hold promise for improved diagnostics, optimized treatment regimens, and provide better patient outcomes in the future where drug-resistant TB in WA can be effectively controlled, reducing the burden of the disease, and improving the health outcomes of affected individuals.